Polemik Jangka Waktu Pengajuan Gugatan Ke Pengadilan Tata Usaha Negara - Marvin, Renius Albert; Erliyana, Anna, Prof. (UI Scholars Hub, 2019)
The period of 90 (ninety) days to file a claim in the Administrative Court (PTUN) plays an important role because if the period is passed, the Administrative Decision (KTUN) can not be claimed even if the KTUN contains defects. The basic principle of regulation the period for filing a claim to the Administrative Court is determined explicitly in Article 55 of the Law of Administrative Courts, which is 90 (ninety) days after the KTUN is received or announced which can be applied in several variables that prove the opportunity for everyone can take legal action if the Administrative Decision issued has violated the laws and regulations and the principles of good governance. However, the time limit for filing a claim to the Administrative Court is also felt to have hurt the sense of justice and limits human rights to defend their legal rights and interests.